(untitled) (Research, Society and Development, 2020)
The present study investigated the effects of the application of combined therapy in a pulsed manner associated or not with the medium-frequency excitomotor current in women for the treatment of localized fat reduction, effects on blood pressure and on the autonomic nervous system. This is a clinical trial randomized study, made up of women who underwent combined therapy treatment over 12 combined. The variables analyzed were anthropometry, heart rate variability and blood pressure. With a decrease in localized fat in the group with an association of excitomotor current, HRV did not yield results, suggesting future studies with the cardiac population.